The andrographolide derivative, AND7, and TRAIL combination attenuates acute lymphoblastic leukemia through P53-regulated ROS accumulation - Letian Xu; Yuting Zhou; Rui Ma; Xinqin Guo; Hao Chen; Lei Fan; Xiaoming Wang (Acta Materia Medica, 2024)
Acute lymphoblastic leukemia (ALL) is a malignant disease of the hematologic system. The current treatment is based on chemotherapeutic drugs, which are becoming less effective due to drug resistance. TNF-related apoptosis-inducing ligand (TRAIL) is an apoptotic protein used to treat cancer that does not affect healthy cells. In recent years, however, ALL cells (e.g., U937) have become more resistant to TRAIL. A novel andrographolide derivative (AND7) with high efficiency and low toxicity was synthesized and combined with TRAIL after the optimal combination ratio was screened using U937 cells. We used peripheral blood mononuclear cells (PBMCs) from patients before the initial treatment of ALL as a model and PBMCs from healthy subjects as a control to determine the mechanism underlying ALL treatment. AND7/TRAIL combination treatment was shown to prevent the original TRAIL-resistant cells from activating the caspase-8/caspase-3 pathway through DR4/DR5 and promote apoptosis via expression of ROS and the apoptotic gene, P53, to achieve an anti-cancer effect. Notably, this study demonstrated that the AND7/TRAIL combination enhanced the anti-cancer effect of AND7 and improved TRAIL resistance. Therefore, the AND7/TRAIL combination is promising for treating ALL and lays the foundation for clinical research.